OVERVIEW OF THE TEMPORARY MEASURES FOR REDUCING THE IMPACT OF CORONAVIRUS DISEASE 2019 (COVID-19) ACT 2020 - Rohana Abdul Rahman (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The impact of Coronavirus disease has transcended beyond imaginable. Everyone is vulnerable and no one on this planet can safely say that he or she is protected against the deadly virus. All governments are taking immediate steps to address the ensuing repercussion of the pandemic, both on short term and long-term basis. Malaysia has passed a law that provides for temporary measures to reduce the impact of COVID-19 on the general economic sectors affecting the general economic well-being of the country. This paper explains the provisions of the COVID-19 Act 2020 and the specific other laws that it intends to modify therein. In particular, the paper highlights the establishment of a mediation process in respect of disputes arising from the inability to perform contractual obligations by parties during the pandemic. The paper concurs that COVID-19 Act 2020 attempts to cover quite comprehensive temporary measures to address issues relating to the pandemic and in the process provides validity to the actions taken by various parties before its commencement. On the other hand, the paper argues that several vague and uncertain provisions of the law led to questionable application and implication thus creating doubts as to its effectiveness.